2009
DOI: 10.1016/j.ejvs.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Modern Treatment of Juxtarenal Abdominal Aortic Aneurysms with Fenestrated Endografting and Open Repair – A Systematic Review

Abstract: Selective f-EVR appears to have reduced peri-operative mortality compared with traditional open surgery, yet selectivity within the study groups and lack of a rigorous classification prohibit more robust comparison. Promising short-term results confirm a role for f-EVR in management of complex abdominal aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 38 publications
0
127
0
Order By: Relevance
“…Some designs are without fenestrations but with branches (pre-attached limbs or cuffs) targeted for the visceral aortic vessels, suitable for the endovascular treatment of thoracoabdominal aortic aneurysms (TAAAs). At least for short-necked and juxtarenal aortic aneurysms (JRAs), fenestrated stent-grafting technology has been shown to be feasible, [12][13][14][15][16][17][18][19][20] with published results of highvolume experienced single centers [21][22][23][24][25][26][27][28][29][30][31] and a few recent multicenter trials 32,33 sharing remarkable short-and midterm results, with the durability of the technique being satisfactory (technical success > 95%, low mortality rates averaging 1-2% and low rates of mid-term branch vessel occlusion averaging 4-9%). [25][26][27][28][29]34 Other imaginative procedures have also been developed or modified to allow for the segmental or complete coverage of the aorta in the region of vital branches, including the 'chimney', 'snorkel', 'periscope' [35][36][37] and combined endovascular exclusion and extra-anatomic mesenteric/renal bypasses (hybrid visceral revascularization).…”
mentioning
confidence: 99%
“…Some designs are without fenestrations but with branches (pre-attached limbs or cuffs) targeted for the visceral aortic vessels, suitable for the endovascular treatment of thoracoabdominal aortic aneurysms (TAAAs). At least for short-necked and juxtarenal aortic aneurysms (JRAs), fenestrated stent-grafting technology has been shown to be feasible, [12][13][14][15][16][17][18][19][20] with published results of highvolume experienced single centers [21][22][23][24][25][26][27][28][29][30][31] and a few recent multicenter trials 32,33 sharing remarkable short-and midterm results, with the durability of the technique being satisfactory (technical success > 95%, low mortality rates averaging 1-2% and low rates of mid-term branch vessel occlusion averaging 4-9%). [25][26][27][28][29]34 Other imaginative procedures have also been developed or modified to allow for the segmental or complete coverage of the aorta in the region of vital branches, including the 'chimney', 'snorkel', 'periscope' [35][36][37] and combined endovascular exclusion and extra-anatomic mesenteric/renal bypasses (hybrid visceral revascularization).…”
mentioning
confidence: 99%
“…2). Initial experiences with these devices have shown that total endovascular repair is effective and may reduce morbidity rates in patients with arch, thoracoabdominal, pararenal and juxtarenal aneurysms [14][15][16][17][18][19][20][21]. Treatment of chronic type B aortic dissection with the use of fenestrated devices has also been reported with good preliminary results [22,23].…”
Section: Fenestrated and Branched Stent Graftsmentioning
confidence: 99%
“…The patients appear to be at higher risk of failure within the first postoperative year, with a plateau in subsequent follow-up. Secondary intervention rates range between 10 and 20 % are noted in these studies [14].…”
Section: Several Reports Frommentioning
confidence: 99%
“…However, none of them found any RCTs or any comparative studies to answer this question. A systematic review by Nordon et al 51 reported that non-RCTs were identified and they included eight cohort studies reporting 368 fEVAR cases and 12 cohort studies reporting 1164 OSRs of JRAAs. One systematic review by Cross et al 52 identified 11 fEVAR studies describing 660 procedures with no comparison.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%